Metal supported graphene catalysis: A review on the benefits of nanoparticular supported specialty sp2 carbon catalysts on enhancing the activities of multiple chemical transformations - Michael B. Burkholder; Fahim Bin Abdur Rahman; Edward H. Chandler, Jr.; J.R. Regalbuto; B.F. Gupton; J.Meynard M. Tengco (Carbon Trends, 2022)
Transition metal-based heterogeneous catalysts are widely used across many industries. The prevalence of these materials across so many domains has inspired research into many different types of solid supports, the nature of which can affect catalytic performance. One support receiving increased attention because of its many desirable features is graphene. These features include 1) native catalytic properties enabling co-catalysis, 2) enhanced catalytic activity when both metal atoms and nanoparticles are supported, 3) chemical functionalization to tune catalytic properties, 4) tough lattice structure and high electric conductivity, and 5) specific solid-state ligand bond formation augmenting electron transport between graphene and the metal to name a few. Although graphene shows tremendous applicability in heterogeneous catalysis, researchers are still tuning the structure to improve its catalytic performance, such as by incorporating defects or dopants into its morphology. Another important consideration is the interaction between the graphitic support and metal catalyst particle, which in turn is highly dependent upon the nature and quality of the catalyst preparation technique. This work reviews the modification of graphene structure along with the applications of different modified graphene-supported catalysts. It also discusses some of the most used and efficient catalyst preparation techniques for both batch and continuous modes. Various examples of applications that highlight graphene properties and catalytic interactions are discussed. To strengthen our reviews, a set of statistical analysis is included.